The Role of International Adjudicative Bodies in Prosecuting Genocide Crime: A Case Study of International Criminal Tribunal for the Former Yugoslavia (ICTY) - Setiyono, Joko; Roisah, Kholis (International Journal of Criminology and Sociology, 2021)
This paper is intended to explain the urgency of the formation of the International Criminal Tribunal for the former Yugoslavia (ICTY), as an ad hoc international court based on United Nations Security Council (UNSC) Resolution No. 827 of 1993, to try perpetrators of genocidal crimes against ethnic Bosnian Muslims. The crime of genocide originated from the ethnic conflict that occurred in the federation of Yugoslavia. The research was conducted by using a qualitative method, based on analysis of data sourced from international journals, books, and other electronic sources. The results conclude that the genocide that occurred against Bosnian Muslim ethnicity is one form of international crime while threatening international peace and security in the Balkan region, also intended to break the practice of impunity against international criminals who are a common enemy of humanity (hostis humans generis). These two considerations form the legal basis for the issuance of the UNSC Resolution on the Establishment of ICTY. The establishment of ICTY as an international court is intended as a court used to try perpetrators of genocidal crimes against Bosnian Muslim ethnicities, so that similar crimes will not be repeated in the future, both in Yugoslavia and in various other countries.